Evaluating the Effects of Mergers on Financial Performance: Evidence from Nepalese Commercial Banks (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study investigates the impact of the merger between two Nepalese banks on their financial performance, with the objective of assessing whether significant improvements in key financial metrics occurred post-merger. The research aims to provide insights into the effectiveness of mergers in enhancing the financial health and operational efficiency of banks in Nepal.Methods: A causal comparative research design was adopted, analyzing secondary data from the banks’ financial statements and regulatory filings for the period 2016/17 to 2022/23. The study focused on key financial metrics, including Return on Assets (ROA), Net Profit Margin (NP Margin), Capital Adequacy Ratio (CAR), Debt to Equity Ratio (DE Ratio), and Debt to Assets Ratio (DA Ratio). Data analysis involved a comparison of the pre-merger and post-merger performance to assess improvements.Results: The findings indicate that, following the merger, both banks experienced significant improvements in their financial metrics. Notably, the merger led to enhanced operational efficiency, increased profitability, and a stronger capital base, highlighting the positive impact of mergers on bank performance.Conclusion: This research contributes to the limited frame of knowledge on mergers and acquisitions in Nepal, emphasizing the strategic importance of such activities in the banking sector. It also addresses gaps in understanding long-term effects.